Contribuição para uma metodologia de desenvolvimento de referências de tensão contínuas programáveis - Valdenio Miranda de Araujo (2009)
Devices for voltage references initially used as standards for laboratory equipment calibration consisted of high-cost units which included Clark cells, Weston cells and some types of batteries with restrictive requirements on operation conditions such as temperature controlled.Alternative to the above devices of voltage references areemiconductor-based devices. They present voltage characteristics of stability comparable to standard laboratory calibration equipment.These alternative devices depend on the characteristics of semiconductor elements to operate with such stability. The goal of this study is to evaluate the technical implementation of voltage reference devices in the environment of a typical research and development laboratory of electronic applications. This assessment includes the development of a methodology for specification, simulation and construction of benchmarks of reference voltage generated from solid-state devices at low cost and easy operation. These standards should be used for calibration and measurement equipment check-up. Two distinct techniques for the synthesis of continuous voltage are evaluated in this study: digital to analog conversion using a digital to analog converter (D/A) with an effective resolution of 20-bit and conversion for pulse width modulation (PWM conversion) withan effective resolution of 20 bits. Both systems work as closed loop circuit. The system control strategies are intended to minimize the errors inherent to the components used in the system.